KEUTUHAN CIPTAAN DAN KELESTARIAN LINGKUNGAN HIDUP DITINJAU DARI SEGI ETIKA KRISTEN - Rencan Carisma Marbun (Institut Agama Kristen Negeri Tarutung, 2018)
AbstracThe environment has a very important life support function. Therefore, management and development are directed to maintain its existence in a dynamic balance through various safeguards and rehabilitation efforts and also the efforts to maintain balance between its elements continuously. Furthermore, it is necessary to improve the harmony of the population and the environment, develop environmental awareness, and encourage participation and self-help of the community in preserving the ability of life (preserving the environment). The attitude and mentality of human who are not aware of the meaning and function of the environment, as well as the meaning of humanity as God's creation have caused various problems in the environment. Humans are given the mandate by God to guard, account for in their use and maintenance, because humans are the highest creation of God from other creations. This paper will describe the meaning of the integrity of creation and environment, the basis of theology about the integrity of creation and environment, problems about the environment, attitudes and responsibilities of Christians about the integrity of creation and environmental sustainability, analysis and conclusion.